ChemInform Abstract: Design and Synthesis of Some New N‐Phenylanthranilic Acids from Highly Sterically Hindered Anilines. Issue 29 (1st July 2013) - Li, Zhenghua; Chen, Gang; Qiao, Shu; Liang, Ronghui; Lan, Cong; Xia, Zhining
Abstract: A series of new N‐arylanthranilic acids of type (III) are prepared from 2‐chlorobenzoic acids and sterically hindered aniline derivatives using copper(I) iodide as catalyst.